Problematics Intellectual Property Rights of Music Industriallization Indonesia After The Easy Trying of Creating Work - Habibi, Muhammad (Pancasila and Law Review, 2022)
In 2020, the Indonesian government, under President Joko Widodo, enacted job creation regulations aimed at stimulating the national economy. However, these regulations faced significant opposition due to concerns about their potential negative impact on Intellectual Property Rights (IPR). While the Copyright Act provides some protection for intellectual property, it is not comprehensive. This gap has led to notable issues in the music industry, particularly with copyright infringements by cover singers on YouTube. This research employs a normative approach, utilizing both statutory and conceptual analyses. The findings reveal that the existing Government Regulations, designed to facilitate business operations, have been insufficient in addressing the challenges posed by YouTube users who infringe on copyrights of songs produced by national music industry entities. To address this issue, it is recommended that the government revise Government Regulation Number 56 of 2021 concerning Song and Music Royalties to enhance legal protection for Indonesian songwriters against piracy of their works by cover singers on YouTube.